1973
DOI: 10.1172/jci107494
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of Sphincter Action. STUDIES ON THE LOWER ESOPHAGEAL SPHINCTER

Abstract: A B S T R A C T The purpose of this study was to evaluate the mechanical factors involved in the genesis of lower esophageal sphincter pressure. We determined the relationship between intraluminal pressure and inside diameter, estimated the ratio between the wall thickness to inside radius, and calculated the tension in the wall of the lower esophageal sphincter as a function of the inside diameter. Various degrees of circumferential stretch were applied by introducing probes of different diameters in the rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Because force of closure and tension continue to increase within the range tested, the diameter of optimum tension development is larger than 1 cm and far from closure. These observations are in complete agreement with the data obtained in the rat LES (3).…”
Section: Introductionsupporting
confidence: 93%
“…Because force of closure and tension continue to increase within the range tested, the diameter of optimum tension development is larger than 1 cm and far from closure. These observations are in complete agreement with the data obtained in the rat LES (3).…”
Section: Introductionsupporting
confidence: 93%
“…Recent developments have allowed the use of micromanometric evaluation of aerodigestive reflexes in preterm infants ( 9 12 ), as well as the longitudinal assessment of these neuromotor markers relevant to the esophageal sphincters and esophageal body ( 13 16 ). The upper esophageal sphincter (UES), a conglomeration of skeletal muscles, and the lower esophageal sphincter (LES) constituted by highly specialized smooth muscle, ( 17 20 ) provide important barrier functions for airway protection and esophageal clearance during swallowing and GER events. Specifically, aerodigestive protective reflexes such as UES contraction safeguards against retrograde GER ascent, and LES relaxation facilitates luminal clearance during peristalsis.…”
Section: Introductionmentioning
confidence: 99%
“…Force–velocity analysis demonstrated that both the work and power generated during esophageal and LES muscle contraction were determined by (1) the initial muscle length produced by the preload, (2) the afterload against which the muscle was contracting, and (3) the contractility of inotropism of the muscle . The tension–diameter curves of the LES muscle showed that optimal tension development did not occur at or near sphincter closure but at much wider diameters . Swallow and esophageal distension can induce LES relaxations due to axial stretch …”
Section: Normal Esophageal Anatomy Function and Biomechanical Propementioning
confidence: 99%
“…55 The tension-diameter curves of the LES muscle showed that optimal tension development did not occur at or near sphincter closure but at much wider diameters. 56 Swallow and esophageal distension can induce LES relaxations due to axial stretch. 57…”
Section: Normal Esophageal Anatomy Function and Biomechanical Propementioning
confidence: 99%